Struggling for One's Name: Defense Narratives by those Accused of Small-Time Corruption. Issue 2 (2nd April 2016) - Åkerström, Malin; Wästerfors, David; Jacobsson, Katarina
ABSTRACT: Under scrutiny (what we term a "bribery gaze"), many interpersonal exchanges in work contexts are perceived as bribes rather than gifts, tokens of appreciation, or mundane favors. Current Swedish bribery laws are strong, and the media keep a vigilant eye out for suspicious activities. From a wide set of qualitative data, we selected 13 interviews with formally-accused middle managers and low-level officials in Sweden who claimed to be innocent of small corruption. We discovered that they were more concerned with defending their honor than with job losses, material losses, or legal repercussions. The interviewees used a contrast structure: While they defined the humiliating accusations and disproportionate measures as turning points, they narrated their moral struggles and claimed their innocence by retelling significant events. These personal narratives from those accused of corruption showed that honor remains very important in contemporary society.